Re-mapping urban vitality through Jane Jacobs' criteria: The case of Kayseri, Turkey - Pakoz, Muhammed Ziya; Yaratgan, Dilara; Sahin, Aydan (Elsevier Sci Ltd, 2022)
There has been a growing debate in recent decades about the view of city and urban theory. The scope of this discussion has expanded with many different claims about the variable structure of the city and urban society, the boundaries of the urban scale, the nature of the city and urban problems. Jane Jacobs, one of the focal points of these discussions, has offered a different perspective with the approach of urbanism and the principles shaping the city's reconstruction: More important than how cities look is how they work. Therefore, human interactions which create a vibrant environment in cities should be considered to understand the dynamics of cities. Located in the central part of Turkey, the city of Kayseri is a rapidly growing industrial city with approximately 1.4 million population. Despite the fact that the city has a long history, the traditional urban pattern has been largely destroyed via planning decisions and the vast majority of the housing stock in the city has been renewed in the last 40-50 years. This paper examines the city of Kayseri using Jane Jacobs' criteria for what makes a city livable and vibrant. We re-mapped 87 neighborhoods of the city that constitute a continuous urban macroform by using the Kernel Density tool with ArcGIS software, evaluated the urban vitality of each neighborhood, and compared outputs with our observations to understand the relevance of Jacobs' views in different contexts. The main findings of the study reveal that not only historical and commercial centers within the city but also several transformed and newly built areas have high urban character values according to Jacobs' criteria. However, the degree of vitality (high, moderate, low, or non-urban), which is measured, may differ from the urban vitality, which is observed by the naked eyes in some neighborhoods of the city.
Keywords: Jane Jacobs; Urban vitality; Kayseri; Kernel Density